Going Green of Mission and Vision Statements: Ethical, Social, and Environmental Concerns across Organizations - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
Mission and vision statements are a critically important piece of business communication from an organization to all of its stakeholders [1]. Today, it is quite easy for even a small company to create a website and sell goods all over the world and most companies around the world have increasingly adopted mission statements with corporate values as a top issue on their agendas. These mission and vision statements must be constantly revised and modified in response to changes within the organization and its environment [1]. In contrast to traditional strategic management approaches, today's companies have focused on the social strategy activities, such as philanthropy, corporate values for having the competitive advantage [2]. Therefore, social responsibilities should also be considered to include concerns for social factors and the environment within the missions of the companies [3]. Personal and ethical values constitute the basis of their mission statements with an emphasis of the strategy formulation along with the significance of international or global operations [4]. Following the information that the natural environment is an increasingly salient component of the global commercial environment as is reflected in growing academic and practitioner interest in corporate management of environmental issues [5], going green is analyzed in current mission and vision statements as the basic emphasis which acquires the definition of involving the concepts of ethical behavior, social responsibility and protection of the environment. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: Mission statement; vision statement; green; corporate social responsibility; environmental sensitivity; ethics; CORPORATE; RESPONSIBILITY